Governança corporativa em organizações públicas: o caso das prefeituras da mesorregião centro ocidental Rio-Grandense - Ramos, Schirlei Stock (2014)
The demand for more Legality, Impersonality, Morality, Publicity and Efficiency (LIMPE) in governmental actions, especially in the municipalities, is directly related to the question of the development of cities. However the limits arise when the actors involved in public governance do not appropriate these concepts enough, resulting in negative impacts on the lives of all citizens. The present study using descriptive statistics analyzes corporate governance in the city halls of the 31 municipalities that make up the western center mesoregion of Rio Grande do Sul, presenting the perceptions of public managers regarding LIMPE and its applicability in managerial governance practices. The analysis characterizes the essential elements that tangibilize the constitutional guiding principles of the Brazilian Public Administration, and presents the theoretical-conceptual model built for the evaluation of the corporate governance of the analyzed city halls. The application of the proposed model can be replicated in the 5,564 Brazilian municipalities, considering that it is rooted in the very foundations of the legal management (conditioned to LIMPE) and in contemporary management practices applicable specifically to the nature of Direct Administration (as is the case of city halls). As for the results obtained from the application of the proposed instruments, empirical data show that Center Western mesoregion of Rio Grande do Sul has a corporate governance classified as median. Also, we alert also to the evidence that the Learning and Growth perspective exactly as defined in the instrument obtained in Center Western mesoregion of Rio Grande do Sul the lowest average among the factors and is below the sufficiency parameter defined in the study. Finally, propositions able to contribute and alleviate the reality found are presented.